Ocrelizumab reduces progression of upper extremity impairment in patients with primary progressive multiple sclerosis: Findings from the phase III randomized ORATORIO trial. (December 2018) - Fox, Edward J; Markowitz, Clyde; Applebee, Angela; Montalban, Xavier; Wolinsky, Jerry S; Belachew, Shibeshih; Fiore, Damian; Pei, Jinglan; Musch, Bruno; Giovannoni, Gavin
Background: Upper extremity (UE) impairment is common with primary progressive multiple sclerosis (PPMS). Objective: This exploratory analysis examined the effects of ocrelizumab on confirmed progression (CP) and confirmed improvement (CI) in UE impairment in patients from ORATORIO. Methods: Patients with PPMS received ocrelizumab 600 mg or placebo every 24 weeks for ⩾120 weeks. The Nine-Hole Peg Test (9HPT) was administered at baseline (BL) and every 12 weeks thereafter. Prespecified exploratory endpoints included change in 9HPT time and proportion of patients with CP of ⩾20% in 9HPT. Analysis populations included intention-to-treat (ITT) patients and subgroups stratified by BL 9HPT time and Expanded Disability Status Scale. Post hoc analyses included the proportion of patients achieving more severe thresholds of CP and the proportion achieving CI in 9HPT. Results: Among ITT patients, ocrelizumab significantly reduced the change in 9HPT time over 120 weeks, the risk of CP of ⩾20% in 9HPT time for both hands and the risk of more severe 9HPT progression versus placebo. Numerical trends also favoured ocrelizumab versus placebo with respect to achieving CI. Consistent directional trends were observed in subgroup analyses. Conclusion: Ocrelizumab reduces the risk of UE disability progression and may increase the possibility of improvement versus placebo in PPMS.